Assessing the Needs of the SMA Population: Survey Results of Health Care Providers and Families. (27th November 2014) - Halanski, Matthew A.; Patterson, Karen G.; Sund, Sarah A.; Makholm, Linda M.; Schroth, Mary K.
To define issues of greatest importance to families and health care professionals (HCP) involved in caring for patients with spinal muscular atrophy (SMA), an electronic survey was distributed to patients, families, and HCPs to determine the most important issues facing patients with SMA. Seventy-seven patients/families (30 SMA type I, 36 SMA type II, 11 SMA type III) and 89 HCPs (17 pulmonologists; 10 physical, speech, and occupational therapists; 19 orthopedic surgeons, 12 neurologists; 13 nurses; 10 nutritionists; 8 others) completed the survey. Breathing issues, impact of diet, impact of disease on the family, spinal deformity, and surgical interventions were the five most frequently identified topics in order of importance to the patients/families. Important topics were similar for the HCP ranking those as follows: breathing issues, impact on family, spinal deformity, impact of diet, and impact of medications. This investigation reports the current most important perceived health care needs of patients with SMA. The perceived needs were similar between patients, families, and HCPs.